2017
DOI: 10.1080/1828051x.2017.1403296
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimates of genetic parameters and genetic trends for morphometric traits and their relationship with yearling weight in Moghani sheep

Abstract: This study was conducted to estimate variance components, genetic parameters and genetic trends for morphometric traits and their relationship with yearling weight in Moghani sheep. The data set and pedigree information of Moghani sheep were obtained from the breeding station of Moghani sheep (in Ardebil province, Iran) and comprised 2387 lamb records for morphometric traits during 1994 to 2012. Traits considered were height at withers (HW), height at rump (HR), body length (BL), heart girth (HG), leg circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Estimates of genetic correlations between BW and CG, BL and HW are high, suggesting these indicator traits could be used to indirectly select for better growth. As it has been reported elsewhere [22,43], the most important correlation was found between BW and CG (0.79). This may be because GC and BW are both tissue-related measurements while BL and HW are skeletal-related measurements [44].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Estimates of genetic correlations between BW and CG, BL and HW are high, suggesting these indicator traits could be used to indirectly select for better growth. As it has been reported elsewhere [22,43], the most important correlation was found between BW and CG (0.79). This may be because GC and BW are both tissue-related measurements while BL and HW are skeletal-related measurements [44].…”
Section: Discussionsupporting
confidence: 80%
“…Output of the iterations were used to calculate the mean, median, and highest posterior density (HPD) interval for each variance/covariance components [18,21,22]. Phenotypic variances (σ 2 ph ) of body weights and linear measurements were computed as: σ 2 ph = σ 2 a + σ 2 m + σ 2 p + σ 2 c + σ 2 e .…”
Section: Bayesian Estimationmentioning
confidence: 99%
“…In this same study, the authors found genetic correlations between body height and chest circumference ranging from 0.39 to 0.68. Estimates of genetic correlation between RH and chest circumference of 0.46 and 0.38±0.22 were obtained, respectively, by Jafari and Hashemi [ 26 ], in Makuie sheep, and by Hossein-Zadeh and Ghahremani [ 27 ], in Moghani sheep.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first research report to evaluate different non-linear models for representing WH and BW:WH growth curves in different breeds of dairy heifer. Measurements of morphometric parameters are highly beneficial to breeders for identifying appropriate animals at an earlier stage of growth for selection purposes (Ghavi Hossein-Zadeh and Ghahremani, 2018). Regarding variation in WH during the first 24 months of age, Kertz et al .…”
Section: Discussionmentioning
confidence: 99%